Extraction and amplification of DNA from orchid exsiccates conserved for more than half a century in a herbarium in Bogotá, Colombia - Mazo, Laura C.; Gómez, Alberto; Quintanilla, Sonia R.; Bernal, Jaime E.; Ortiz Valdivieso, Pedro (Lankesteriana: International Journal on Orchidology, 2013)
Plant tissue from herbarium specimens contains DNA that has undergone post-mortem degradation. Only small amounts of possibly degraded genetic material free of chemicals and impurities can be extracted from these samples. The aim of the present work was to compare and determine which one of three previously published plant DNA extraction protocols would extract good quality DNA from orchid herbarium specimens stored up to 63 years, susceptible of PCR amplification and Sanger sequencing. The most effective protocol for this type of samples allowed us to obtain and sequence amplified products in 6 of the 7 samples studied with an optimal DNA / protein purity relationship.